SYNTHESIS OF ARTIFICIAL GRAVITATIONAL FIELDS VIRTUAL METERS FOR THE POLYCONFLICTS RESOLUTION IN THE AERONAVIGATION ENVIRONMENT - Chepizhenko, Valery (Proceedings of National Aviation University (archive), 2012)
In article schemes have been offered and characteristics of virtual meters of artificial force fields for the conflicts resolution in the aeronavigation environment have been investigated.